Core principles and applications of corporate finance - ROSS, Stephen A (McGraw - Hill Book Company, 2007)
The integrated solutions for Ross/Westerfield/Jaffe/Jordan's Corporate Finance: Core Principles and Applications have been specifically designed to help improve student performance, meaning that students are prepared for and engaged in class, and they can successfully solve problems and analyse the results. McGraw-Hill's adaptive learning component, LearnSmart, provides assignable modules that help students master chapter core concepts and come to class more prepared. In addition, resources within Connect help students solve financial problems and apply what they've learned. Ross' focus on the core concepts, cutting-edge research, and rich problem material combine with a complete digital solution to help students achieve higher outcomes in the course. Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need, when they need it, and how they need it, so that your class time is more engaging and effective